THE COMPARISON OF STUDENT INTEREST AND LEARNING OUTCOMES USING DIFFERENTIATED LEARNING IN CONTENT AND PROCESS - Yulianti, Delfita (Universitas Mahaputra Muhammad Yamin, 2024)
The goal of this study is to compare students' interests and learning outcomes when using content and process differentiated learning. To determine the difference, experimental study utilizing a factorial design was used. The purposive samples for this study were students in grades XI F2 and XI F4 who picked English as an elective subject. XI F2 was taught using differentiated learning in process, whereas XI F4 was taught using differentiated learning in content. A questionnaire was utilized to collect data on learning interests, and the data were analyzed using average calculations. Learning outcomes were analyzed using one-way ANOVA. Questionnaires and students' first and second semester learning outcome ratings were utilized as the research instrument for the study. The finding of this study is that there is no significant difference of students’ interest and learning outcomes using differentiated content and process. The result highlights that differentiated instruction has a powerful method for enhancing student interest and learning outcomes.